Cultural Diversity in Large Enterprises: A Qualitative Analysis from the Alpine Rhine Valley. Issue 5 (29th July 2019) - Kraus, Sascha; Schleich, Moritz; Tröster, Andreas; Roig-Tierno, Norat
Abstract: International expansion requires specific management methods to adapt to differences between cultures, thus requiring global strategies that ensure efficient diversity management. The increasing diversity in the workforce is thus gaining more importance in determining knowledge of efficient and better business performance. The results of the study illustrate the importance of cultural diversity and the high benefits for companies. The key findings are a high degree of creativity, a practical understanding of the market, better access to international markets, a high degree of linguistic diversity and efficient innovation management. The starting point of cultural diversity lies in the respective corporate cultures.